Action potential contour contributes to species differences in repolarization response to β-adrenergic stimulation. Issue 9 (17th October 2017) - Sala, Luca; Hegyi, Bence; Bartolucci, Chiara; Altomare, Claudia; Rocchetti, Marcella; Váczi, Krisztina; Mostacciuolo, Gaspare; Szentandrássy, Norbert; Severi, Stefano; Pál Nánási, Péter; Zaza, Antonio
Abstract: Aim: Repolarization response to β-adrenergic (β-AR) stimulation differs between guinea-pig and canine myocytes and, within the latter, between myocardial layers. Correlative analysis suggests that this may be due to differences in action potential (AP) contour. Here we tested whether AP contour may set the response of current and of repolarization to β-AR stimulation (10 nM isoproterenol, ISO). Methods and results: The responses of AP and current to ISO were measured under I-clamp and "AP-clamp" in guinea-pig (GP), dog epicardial (DEPI) and dog subendocardial (DENDO) myocytes. Dynamic-clamp (DC) was used to evaluate the impact of AP features on AP response to ISO. ISO prolonged AP duration (APD) in GP myocytes, did not affect it in DENDO and shortened it in DEPI ones. The current induced by ISO (IISO ) sharply differed between GP and canine myocytes and, to a lesser extent, between DENDO and DEPI ones. Differences in IISO profile likely important in setting APD response (time-to-peak, time-to-reversal), were minimized when canine myocytes where clamped with GP AP-waveforms and vice versa. Introduction of a "notch" in GP AP (by DC) was alone insufficient to affect the APD response to ISO; nevertheless, when incorporated in a GP AP-waveform, the main "canine" AP features ("notch" and low plateau potential) caused IISO of GP myocytes to acquire canine features. Conclusion: Early repolarization contour and level of plateau potential contribute to species-specificity of IISO profile. Changes in AP contour, also when generated by modulation of ISO-insensitive currents, may be crucial in setting APD response to β-AR stimulation.